2020
DOI: 10.1109/toh.2019.2949411
|View full text |Cite
|
Sign up to set email alerts
|

Tactile Perception of Virtual Edges and Gratings Displayed by Friction Modulation via Ultrasonic Actuation

Abstract: To render tactile cues on a touchscreen by friction modulation, it is important to understand how human perceive a change in friction. In this study, we investigate the relations between perceived change in friction on an ultrasonically actuated touchscreen and parameters involved in contact between finger and its surface. We first estimate the perceptual thresholds to detect rising and falling friction while finger is sliding on the touch surface. Then, we conduct intensity scaling experiments and investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 91 publications
(71 reference statements)
1
5
0
Order By: Relevance
“…This explains why low- and high-friction zones resulted in similar perceived roughness. Such a result is in line with Saleem et al (Saleem et al, 2020), which showed that period gratings displayed by consecutive sequences of FF followed by RF were perceived with the same acuity as compared to vice versa.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This explains why low- and high-friction zones resulted in similar perceived roughness. Such a result is in line with Saleem et al (Saleem et al, 2020), which showed that period gratings displayed by consecutive sequences of FF followed by RF were perceived with the same acuity as compared to vice versa.…”
Section: Discussionsupporting
confidence: 91%
“…(2017) are different (ultrasonic vs. electrostatic), the perceived roughness in both studies exhibited inverted U-shape trends with varying widths of low-friction and high-friction zones. This may be because the perceived roughness over virtual gratings depends on gratings’ edges (Saleem et al, 2020) and the two device types could generate similar gratings’ edges (E. Vezzoli et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamics of multiple step changes in friction is different from the single one since the interval between the steps is a factor affecting the tactile perception. This topic (multiple step changes in friction) has been already investigated by Vardar et al [18] for electrovibration and Gueorguiev et al [19] Saleem et al [20] for ultrasonic actuation.…”
Section: Discussionmentioning
confidence: 97%
“…Ultrasonic vibration decreases friction force by creating a lubricating squeeze film using surface vibration, whereas electroadhesion increases friction forces using high-voltage electrostatic interaction (typically 100 to 500 V) between fingertips and screens (16,17). The current commercially available devices can achieve 15 to 30% increase over the base friction force with typical voltages of 100 to 200 V (18)(19)(20)(21)(22)(23)(24)(25). Higher friction modulation of up to 43% has also been demonstrated with higher driving voltages of 200 to 500 V (26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%